Research progress of lithium iron phosphate in lithium-ion batteries - Daming SUN; Jie CUI; Xiaojie WANG; Taotao WANG; Ning AN; Heyuan SONG; Haibo JIN (工程科学学报)
Currently, the Earth’s limited resources, the escalating oil crisis, rapid industrial development, and considerable population growth have increased the demand for sustainable energy production and storage systems. A crucial factor in addressing these problems is the development of optimal electrode materials with desirable electrochemical properties. Lithium-ion batteries (LIBs) are the most promising and fastest growing electrical energy storage system. Over the past decade, LIBs have seen substantial growth in industries such as electric vehicles and industrial power generation systems due to their high operating voltage, high specific energy, fast charging and discharging capabilities, wide operating temperature range, long service life, and high environmental safety. LIBs primarily comprise cathode materials, anode materials, electrolytes, and diaphragms. Since their commercialization, cathode materials have been a key research focus due to their influence on energy and power density as well as cost. Recent investigations have been exploring lithium battery electrode materials with abundant resources, low cost, and high energy density. Olivine-type lithium iron phosphate (LiFePO4, LFP) is emerging as a potential “green” cathode material for LIBs in the 21st century, focusing on high energy density, long cycle life, low cost, and environmentally friendly. Compared to traditional polyanionic cathode materials, LFP has gained increasing attention due to its high theoretical specific capacity (170 mA·h·g−1), stable voltage platform (3.5 V (vs Li/Li+)), excellent safety performance, and the abundance and low cost of its raw materials. At present, lithium iron phosphate is primarily used in the new energy automotive industry and the energy storage market. Owing to these advantages, LFP has received widespread attention as a promising cathode material for LIBs. However, its lower electronic conductivity and lithium-ion diffusion rate, along with its reduced vibrational density, hinder the electrochemical and low-temperature performance of LFP. These factors lead to lower volumetric energy densities, limiting their further applications to some extent. Consequently, these issues considerably inhibit the development of LFP. At present, improving the conductivity and lithium-ion diffusion rate of LFP has become a key focus of researchers. After years of efforts, researchers have optimized the synthesis process by exploring the charging and discharging principles of LFP. They have also explored various new techniques, processes, equipment, and materials, as well as employing methods such as carbon coating, doping modifications, and nanosizing to enhance LFP performance. This paper outlines the preparation of LFP using six methods: high-temperature solid-phase method, carbothermal reduction method, sol–gel method, hydrothermal synthesis method, coprecipitation, and microwave methods. The paper also discusses the advantages and disadvantages of each preparation method. Various modification strategies for LFP, including carbon capping, ion doping, nanosizing and the use of quantum dots, are also comprehensively reviewed. Additionally, five recycling methods are described: hydrometallurgy, pyrometallurgy, high-temperature solid-phase remediation, bioleaching, and direct regeneration. Finally, the paper offers an outlook on the future development trends of LFP.